Rebranding the visual identity design of Chinese online casual menswear brands based on super symbols - Jundi, Dai; Daimin, Ghazali; Bakar, Muhammad Fauzan Abu (International Journal of Asian Social Science, 2024)
This article aims to explore a new domain within China's online casual menswear industry, proposing a comprehensive conceptual framework to address the complexities inherent in this vibrant sector. At its core is the innovative concept of "super-symbols," envisioned as tools for crafting visually striking and iconic expressions. These super-symbols are designed to shape a new brand identity, capturing not only consumer sentiments but also transcending traditional boundaries to make a lasting impact in the fiercely competitive market. By delving into unique cultural and aesthetic characteristics, the framework identifies elements that resonate with the target consumer base. Grounded in semiotic theory and visual identification principles, the study employs a qualitative research approach to construct a brand visual model. This involves a methodology of literature review, in-depth interviews, and thematic analysis, with coding facilitated by Nvivo software. Integrating theoretical insights with practical applications, this research offers guidance for a nuanced and culturally appropriate methodology for brand rejuvenation. This meticulous framework provides crucial resources for designers and marketers, assisting them in thriving within the ever-evolving landscape of China's online fashion market.